Physicochemical, textural and viscoelastic properties of palm diacylglycerol bakery shortening during storage - Cheong, Ling Zhi; Tan, Chin Ping; Long, Kamariah; Yusoff, Mohd Suria Affandi; Lai, Oi Ming (Society of Chemical Industry, 2010)
BACKGROUND: Diacylglycerol (DAG), which has health-enhancing properties, is sometimes added to bakery shortening to produce baked products with enhanced physical functionality. Nevertheless, the quantity present is often too little to exert any positive healthful effects. This research aimed to produce bakery shortenings containing significant amounts of palm diacyglycerol (PDG). Physicochemical, textural and viscoelastic properties of the PDG bakery shortenings during 3 months storage were evaluated and compared with those of commercial bakery shortening (CS).